Conexiones Culturales y Patrimonio Prehistórico - Garrido Anguita, Juan Manuel (2023)
José C. Martín de la Cruz is a pioneer scholar whose contributions both to Prehistory and the diffusion of cultural heritage have been acknowledged at an international level. The present volume pays homage to his professional career, by inviting more than 40 international scholars who tackle the study of Prehistory and the dissemination of heritage from several thematic and temporal perspectives. It is thus a multidisciplinary volume in which scholars from different fields investigate Prehistory from its origins to the period immediately before Greek and Phoenician colonization; at the same time, they explore the different ways in which Prehistoric heritage is transmitted. The volume is composed of four different but related parts, organized chronologically and starting with the most recent Prehistory. The first part deals with the intercultural connections which took place during the Bronze Age in the Mediterranean area. The second part goes back in time and investigates the first settlements and early food producing societies. The third examines our remote past and its natural environment. Finally, the closing part includes a set of multidisciplinary chapters which study prehistory from several different scientific fields. All in all, this volume becomes a scientific meeting point where senior professors and junior scholars get together to offer their scientific findings, at the same time as they pay homage to Professor Martín de la Cruz.